Strategi Kepemimpinan Lafran Pane dalam Memajukan Himpunan Mahasiswa Islam (HMI), 1947 - 1991 - Akla, Abul (Local History & Heritage, 2025)
This study contributes to the academic discourse on student leadership by analyzing Lafran Pane’s strategic approach in advancing the Islamic Student Association (Himpunan Mahasiswa Islam, HMI) from its establishment in 1947 until his passing in 1991. The research examines the leadership strategies employed by Lafran Pane, his motivations for founding HMI, and the broader historical context that shaped his vision. This study employs a qualitative library research method, utilizing descriptive analysis of books, journals, and scholarly articles related to Lafran Pane. The findings indicate that Lafran Pane's leadership strategy was deeply rooted in his nationalistic and religious background, which he synthesized into HMI’s ideological foundation. His efforts to strengthen HMI were driven by Indonesia’s fragile post-independence condition, particularly in governance, religion, and student affairs. As a result, Lafran Pane and his colleagues formulated strategies across education, politics, religion, law, and state administration to solidify HMI’s role as a leading student organization. Ultimately, his leadership model emphasized character development, which became a fundamental trait embedded in all HMI cadres, ensuring the organization's resilience and ideological continuity.